Pharmacokinetics of clenbuterol in the ostrich - van der Merwe, P J; Toerien, S; Burger, W P (Analyst (London), 1998)
The aim of this study was to investigate the pharmacokinetics of clenbuterol in the ostrich as no such data is available. Clenbuterol (2 mg) was given as a single oral dose to nine ostriches. Blood samples were collected over a period of 96 h after administration and urine for a period of 5 d. Plasma and urine samples were frozen at -20 degrees C pending analysis. Clenbuterol was quantified using a gas chromatograph-mass selective detector. The method for quantification of clenbuterol in plasma was validated by analysing spiked quality control samples at different concentrations. The limit of quantification was determined to be 0.75 ng ml-1 with an absolute recovery of more than 80%. The geometric mean maximum plasma clenbuterol concentration was 4.40 ng ml-1 with 3.0 h as the median time for maximum concentration. The plasma elimination half-life was 19.7 h. The clenbuterol concentration was above 0.75 ng ml-1 in plasma for 48 h and above 1.0 ng ml-1 in urine for 5 d. These data can be useful in residue analysis for clenbuterol in ostriches.